2016
DOI: 10.1016/j.molcel.2016.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Regulates Chromatin Ubiquitination in DNA Damage Response through Elimination of SQSTM1/p62

Abstract: Autophagy is an intracellular degradation system that delivers cytoplasmic constituents to the lysosome, and loss of autophagy has been linked to increased genome instability. Here, we report that loss of autophagy is coupled to reduced histone H2A ubiquitination after DNA damage. p62/SQSTM1, which accumulates in autophagy-defective cells, directly binds to and inhibits nuclear RNF168, an E3 ligase essential for histone H2A ubiquitination and DNA damage responses. As a result, DNA repair proteins such as BRCA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
154
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(168 citation statements)
references
References 53 publications
14
154
0
Order By: Relevance
“…Through the ability of p62 to interact with TRAF6, p62 activates NF-κB (14). Recently, p62 has been shown to promote genomic instability by slowing the repair of DNA double strand breaks, thereby promoting error prone nonhomologous end joining (NHEJ) (15). p62 also sequesters Keap1 from Nrf2 and promotes activation of the antioxidant transcription pathway (1618), while also acting as a direct positive regulator of mTORC1 through interactions with Raptor and the Rag proteins in the amino acid-sensing pathway (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Through the ability of p62 to interact with TRAF6, p62 activates NF-κB (14). Recently, p62 has been shown to promote genomic instability by slowing the repair of DNA double strand breaks, thereby promoting error prone nonhomologous end joining (NHEJ) (15). p62 also sequesters Keap1 from Nrf2 and promotes activation of the antioxidant transcription pathway (1618), while also acting as a direct positive regulator of mTORC1 through interactions with Raptor and the Rag proteins in the amino acid-sensing pathway (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…1 An analysis of chromatin protein extracted from HeLa cells, revealed that SQSTM1 knockdown increases chromatin poly-ubiquitination. Conversely, overexpression of SQSTM1 has the opposite effect, reducing this DNA-damage-induced chromatin ubiquitination.…”
mentioning
confidence: 99%
“…In addition, in the absence of autophagy IR failed to induce RNF168, BRCA1, RAP80, and Rad51 foci formation; however, the foci were recovered in p62 knockdown cells. These observations indicate that p62 is a physiologic modulator of DNA repair 9 (Fig. 1).…”
mentioning
confidence: 71%